L’architecture comme expérience totale : autour d’une restitution informatique de la salle de lecture de la bibliothèque Sainte-Geneviève d’Henri Labrouste - Bressani, Martin; Grignon, Marc; Albloushi, Adel (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2013)
Henri Labrouste’s Bibliothèque Sainte-Geneviève (1851) is recognized as one of the major monuments of nineteenth-century Paris. Its magnificent reading room, generally well preserved, has been subjected to a number of transformations over the years. Though its initial form is known from old photographs showing the interior space during daytime, the authors of this article have sought to reconstruct the original reading room in a 3D digital model that would render the atmosphere at different hours. The article first explains how the 3D model was developed, using old photographs, drawings, archives, and the very detailed construction journal kept by the architect. It emphasizes how the night view was produced, with its original system of gas lighting, focusing the light on the working tables, the bookshelves, and the circulation space. The authors then develop the argument that the alternation between natural light and artificial light strongly contributes to the Romantic interpretation of knowledge represented in the library. Situating the Bibliothèque Sainte-Geneviève in relation to other projects in which the alternation of natural and artificial light plays an important symbolic role, such as Boullée’s cenotaph to Newton, they argue that Labrouste’s modernism is not only found in his use of an iron structure in the reading room, but also in his creation of a total architectural experience.